Physio Biochemical Effects of Metformin in Association with Non Insulin Dependent Type 2 Diabetic Patients - Farhan Akhtar, Shmyla Hamid, Aamir Abbas, Sonaina Ehsan, Rizwan Abdul Salam, Khursheed Anwer (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Diabetes happens when your body isn’t able to take up sugar (glucose) into its cells and utilize it for energy. This results in a construct up of additional sugar in your bloodstream. Mismanagement of diabetes can lead to serious results, causing harm to a wide run of your body’s organs and tissues including your heart, kidneys, eyes and nerves. Sedentary way of life and consistent over-nutrition within the past decades, have led to a disproportionate development in type 2 diabetes making this quiet, however debilitating disease a major health predicament within the 21st century. Diabetes mellitus may be divided into numerous different classes such as type 1, diabetes, type 2 diabetes and gestational diabetes mellitus. With ever growing figures, it is anticipated that by 2030, the overall number of individuals with diabetes will rise to 552 million. It is assessed that in 2007 the United States alone, spent 174 billion for diabetes of which 58 billion were attributable to diabetes-related chronic complications. Objective: To determine the effects of association between metformin and type 2 diabetic patients Study design: Open label randomized clinical trial Settings: Garrison Medical centre Jarrar Garrison, Rawalpindi Duration: Six months i.e. 1st January 2022 to 30th June 2022 Data Collection procedure: A single-center, open label randomized clinical trial was conducted. Patients were enrolled through medical OPD Jarrar Medical Center Pakistan from 1st January to June 2022. Patients were selected after falling in the criteria: (1) diagnosis of type 2 diabetes mellitus based on American Diabetes Association (ADA) criteria. (2) No history of serious chronic sicknesses of heart, lung, and kidney. (3) No earlier treatment with anti-diabetes medications for either diabetes or conditions related with hyperglycemia (4) No intake of aspirin within the past year. (5) No history of current or past smoking. Ag pre validated questionnaire was used. The total numbers of patients were 50 who participated after taking the informed consent. The Detailed information was given to patient about the current research. Confidentiality of the participants was prioritized. Results: The total number of patients who participated in the study was 50 in which 30 were males and 20 were females in both groups. There were fifty participants as patients and fifty as control group. There was no gender discrimination in both groups. Baseline characteristics were measured. The others parameters include systolic and diastolic blood pressure, blood sugar fasting, glycemic control and lipid profile was measured. Practical implication Conclusion: This clinical trial of the safety and viability of metformin within the subjects with type 2 diabetes mellitus. In outline, metformin is effective and secure for the treatment of type 2 diabetes. The present finding confirms the ADA’s suggestion to use metformin in type 2 diabetes mellitus patients. Keywords: Metformin, Type 2 diabetes, Exercise, HbA1c, Insulin